Karakteristik Fisik, Kimia dan Tingkat Kesukaan Es Krimalpukat (Persea Americana Mill.) Dengan Penambahan Ekstrakjeruk (Citrus Sinensis L.) - Irul Pamungkas Sari; Chatarina Lilis Suryani; Yuli Perwita Sari (Universitas Mercu Buana Yogyakarta, 2026)
Ice cream is generally made from a mixture of milk, either vegetable or animal fats, sugar, and other additional ingredients. One of the new innovations in ice cream is the use of avocado. Avocado is known for its high fat content but lacks a specific flavor; therefore, baby orange extract, which is rich in vitamin C, is added to enhance the nutritional value and taste of avocado ice cream. This study aims to determine the appropriate addition of baby orange extract to produce avocado ice cream. The experimental design used was a Completely Randomized Design (CRD) with one treatment factor, namely the addition of orange extract (0%, 20%, 40%, 60%, 80%). Each treatment was repeated twice, and data analysis was performed using ANOVA and Duncan's Multiple Range Test (DMRT). The tests conducted included overrun, melting time, viscosity, color, pH, protein content, total sugar, vitamin C, total dissolved solids (TDS), fat content, and preference testing. The results of the study indicated that the best treatment was the addition of 40% orange extract, which had a pH of 6.44%, protein content of 5.65%, total sugar of 3.48%, vitamin C of 9.44%, total dissolved solids of 30.13%, and fat content of 6.43%. The preference levels for color were 4.5 (liked), aroma 3.9 (liked), taste 3.8 (liked), texture 4.05 (liked), and overall 4.1 (liked).